Colonoscopy bowel preparation quality improvement for patients with decompensated cirrhosis undergoing evaluation for liver transplantation. Issue 10 (October 2016) - Clayton, Donnesha B.; Palmer, William C.; Robison, Sarah W.; Heckman, Michael G.; Chimato, Nicolette T.; Harnois, Denise M.; Francis, Dawn L.
Abstract: Background/Aims: Inadequate bowel preparations can necessitate early repeat of colonoscopy and increased healthcare costs. Established risk factors for suboptimal bowel preparation are known, yet data are lacking in the specific subgroup of patients with decompensated cirrhosis. The primary aim of this study was to reduce inadequate bowel preparation rates in patients with decompensated cirrhosis undergoing evaluation for liver transplant via a quality improvement initiative targeting patient education. Methods: A total of 121 patients undergoing evaluation at our institution prior to implementation of the quality improvement initiative and 91 patients undergoing evaluation after implementation were included. The initiative was an educational intervention via a 6‐minute colonoscopy and split‐prep bowel preparation educational video during the initial liver transplantation evaluation visit for all patients with scheduled colonoscopy. Results: Inadequate bowel preparation was observed in 36 patients (29.8%) in the pre‐intervention period compared to 29 patients (31.9%) in the post‐intervention period. This corresponded to a lack of a significant difference in both single‐variable analysis and multivariable analysis. Of note, there was a significantly higher rate of inadequate bowel preparation as ascites worsened ( P =.028). Conclusion: Patient educational video failed to improve bowel preparations in patients undergoing colonoscopy with decompensated cirrhosis.